2011
DOI: 10.3109/00016489.2011.633227
|View full text |Cite
|
Sign up to set email alerts
|

No increased risk of sudden sensorineural hearing loss following recent herpes zoster: a nationwide population-based study

Abstract: Of the sample of 627 224 patients, 121 (0.02%) had SSNHL during the 2-month follow-up period, 59 from the study group (0.02% of the herpes zoster patients) and 62 from the comparison group (0.02% of patients without herpes zoster). Regression analysis revealed no increased adjusted hazard of SSNHL during the 2-month follow-up period for patients with herpes zoster as compared to those without (hazard ratio = 0.89, 95% confidence interval (CI) = 0.63-1.28, p = 0.540).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The etiology and pathogenesis of MD is endolymphatic hydrops [ 22 ], but the etiology and pathogenesis of sudden deafness remain unknown. Proposed theories as to the cause of sudden deafness include vascular occlusion, tearing of the labyrinthine membranes, immune-mediated mechanisms [ 23 ], abnormal cellular stress responses within the cochlea [ 24 ], and viral infection [ 25 ] or reactivation of herpes zoster virus [ 23 ], which are suggested to be influenced by stress hormone due to a physical disorder or fatigue. Thanks to the evacuation centers and temporary housing that were quickly prepared soon after the disaster, victims were comparatively less apt to be physically fatigued.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of MD is endolymphatic hydrops [ 22 ], but the etiology and pathogenesis of sudden deafness remain unknown. Proposed theories as to the cause of sudden deafness include vascular occlusion, tearing of the labyrinthine membranes, immune-mediated mechanisms [ 23 ], abnormal cellular stress responses within the cochlea [ 24 ], and viral infection [ 25 ] or reactivation of herpes zoster virus [ 23 ], which are suggested to be influenced by stress hormone due to a physical disorder or fatigue. Thanks to the evacuation centers and temporary housing that were quickly prepared soon after the disaster, victims were comparatively less apt to be physically fatigued.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported no association between idiopathic SSNHL and HZV infection [9,37]. However, there were several limitations in the previously published studies.…”
Section: Discussionmentioning
confidence: 88%
“…However, there were several limitations in the previously published studies. After being diagnosed with HZ, the follow-up period was only three months [9], or patients who received steroid treatment with HZ oticus were matched [29]. When matching the two groups, it is also important to manage underlying diseases that may affect the patient's immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on basic epidemiological data, the author concluded that sudden deafness was not associated with reactivation of this virus, except in the case of herpes zoster oticus, but sudden deafness may also be associated with hypertension and diabetes. 33…”
Section: Virus Reactivationmentioning
confidence: 99%